(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The current research focuses on ethnomedicinal plants from the Fabaceae family found in theAmarkantak region. The Madhya Pradesh town of Amarkantak is found in the Anuppur district. Indigenouspeoples, including members of the Primitive Tribal Group, form the majority in the district. The climate inthe area is ideal for plant growth, and the forest surrounding Amarkantak is home to a wide range ofmedicinal plants that have been used by the locals for centuries. During my visits to the area, I met localhealers, baigas, and gunias. Plants that they employed for medicinal purposes were given local names.Field visits were then taken to collect and identify wild flora. Plants of the Fabaceae family were chosenand are currently being studied. Presently 23 plant species belonging to family Fabaceae, recorded forethnomedicinal use are Abrus precatorius, Alysicarpus longifolius, Butea monosperma, Canvalia virosa,Clitoria ternatea , Dalbergia lanceolata, Dalbergia latifolia, Desmodium gangeticum Desmodium triflorum,Erythrina stricta, Erythrina variegata, Indigofera cassioides, Indigofera, glandulosa, Melilotus alba,Melilotus indica, Mucuna pruriens, Paracalyx scariosus, Pterocarpus marsupium, Pongamia pinnata,Sesbania bispinosa, Tephrosia purpurea, Tephrosia villosa and Vigna unguiculata.